Physical Activity in the School Setting: Cognitive Performance Is Not Affected by Three Different Types of Acute Exercise - van den Berg, Vera; Saliasi, Emi; de Groot, Renate H. M.; Jolles, Jelle; Chinapaw, Mai J. M.; Singh, Amika S. (Frontiers in Psychology, 2016)
Recent studies indicate that a single bout of physical exercise can have immediate positive effects on cognitive performance of children and adolescents. However, the type of exercise that affects cognitive performance the most in young adolescents is not fully understood. Therefore, this controlled study examined the acute effects of three types of 12-minute classroom-based exercise sessions on information processing speed and selective attention. The three conditions consisted of aerobic, coordination and strength exercises respectively. In particular, this study focused on the feasibility and efficiency of introducing short bouts of exercise in the classroom. One hundred and ninety five students (5th and 6th grade; 10-13 years old) participated in a double baseline within-subjects design, with students acting as their own control. Exercise type was randomly assigned to each class and acted as between-subject factor. Before and immediately after both the control and the exercise session, students performed two cognitive tests that measured information processing speed (Letter Digit Substitution Test) and selective attention (d2 Test of Attention). The results revealed that exercising at low to moderate intensity does not have an effect on the cognitive parameters tested in young adolescents. Furthermore, there were no differential effects of exercise type. The results of this study are discussed in terms of the caution which should be taken when conducting exercise sessions in a classroom setting aimed at improving cognitive performance.